Randomized Trial Comparing Locoregional Resection of Primary Tumor with No Surgery in Stage IV Breast Cancer at the Presentation (Protocol MF07-01): A Study of Turkish Federation of the National Societies for Breast Diseases - GÜLLÜOĞLU, MAHMUT BAHADIR (WILEY-BLACKWELL PUBLISHING, INC, 2009)
The MF07-01 trial is a phase III randomized controlled trial which compares breast cancer patients with distant metastases at presentation who receive locoregional treatment for intact primary tumor with those who do not receive such treatment. The primary objective of the study is to assess whether locoregional treatment of the primary tumor provides a better overall survival. Secondary objectives include progression-free survival, quality-of-life, and morbidity related to locoregional treatment. Locoregional treatments consist of either mastectomy or breast conserving surgery with level I-II axillary clearance in clinically or sentinel lymph node positive patients. Radiation therapy to the whole breast follows breast conserving surgery. Standard systemic therapy is given to all patients either immediately after randomization in no-locoregional treatment arm or after surgical resection of the intact primary tumor in locoregional treatment arm. The study is conducted in Turkey as a multicenter trial with central randomization. Total accrual target is 271. The trial was activated in October 2007 and authorized centers started to recruit patients since then. ClinicalTrials.gov identifier number is NCT00557986.
Keywords: breast cancer; metastasis; randomized trial; surgery; survival; METASTATIC-DISEASE; SURGICAL REMOVAL; SURVIVAL; THERAPY; CHEMOTHERAPY; MANAGEMENT